2019
DOI: 10.1111/jbi.13739
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest type influences community assembly processes in arbuscular mycorrhizal fungi

Abstract: Aim Plant community assembly in tropical rain forest has been shown to be largely governed by stochastic processes, but as arbuscular mycorrhizal (AM) fungi display limited host preference, they may not follow the same stochastic assembly pattern. Here, we determined the relative importance of environmental and spatial drivers responsible for the community assembly process of AM fungi in two types of tropical rain forest: semideciduous rain forest and dense ombrophilous forests. Location Atlantic rain forest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Stochastic processes are reported to dominantly drive plant community assemblies in tropical forests [64], but community assemblies of AM fungi were not always separately governed by stochasticity in natural or disturbed ecosystems [65]. Our results showed that stochasticity was a primary driver of community assemblies of AM fungi in soil and roots.…”
Section: Differential Changing Patterns Of Ecological Processes Drivi...mentioning
confidence: 61%
See 1 more Smart Citation
“…Stochastic processes are reported to dominantly drive plant community assemblies in tropical forests [64], but community assemblies of AM fungi were not always separately governed by stochasticity in natural or disturbed ecosystems [65]. Our results showed that stochasticity was a primary driver of community assemblies of AM fungi in soil and roots.…”
Section: Differential Changing Patterns Of Ecological Processes Drivi...mentioning
confidence: 61%
“…Such an alteration in ecological processes governing AM fungi could be explained by environmental conditions and/or biotic interactions [66]. For example, Pereira et al [65] provided evidence that stochasticity strongly drives AM fungal community assembly in tropical forests and found that environmental factors and species-species interactions exerted deterministic selection on AM fungi. Nitrogen enrichment may result in environmental selection in AM fungal communities and thus enhance the relative importance of determinism.…”
Section: Differential Changing Patterns Of Ecological Processes Drivi...mentioning
confidence: 99%
“…Clearly, further studies are required to cover AMF richness in the hyperdiverse tropical rain forests. Nevertheless, we identified typical taxonomic structures of the AMF communities with the highest abundance of species in the genus Glomus and lower abundances of other fungal genera or families ( Lovelock and Ewel, 2005 ; Davison et al., 2015 ; Vasar et al., 2017 ; Maciel Rabelo Pereira et al., 2020 ). Our plantation roots exhibited one unique AMF species (OTU25, Glomus sp.).…”
Section: Discussionmentioning
confidence: 99%
“…Deterministic processes refer to the biological and environmental selection mechanisms that influence communities, while stochastic processes emphasize dispersal and ecological drift [ 48 50 ]. Previous studies have explored the mechanisms underlying community assembly of individual soil functional groups of fungi in specific ecosystems [ 51 53 ]. For example, Wang et al studied EcM fungal communities of five common pine plant species in Inner Mongolia, China, and the results showed that both deterministic and stochastic processes jointly drove the community association of EcM fungi, but the stochastic process was dominant [ 52 ].…”
Section: Introductionmentioning
confidence: 99%